Happiness among Pregnant Women: A Concept Analysis - Eun Mi Jo; Hyera Yoo (Korean Society of Women Health Nursing, 2016)
PURPOSE: The purpose of this study was to analyze the concept of happiness among pregnant women. METHODS: Walker and Avant's method for concept analysis was used. RESULTS: The defining attributes of happiness among pregnant women were 1) period of pregnancy, 2) emotional dimension (positive affect), and 3) cognitive dimension(existence need-satisfaction, relatedness need-satisfaction, growth need-satisfaction). The antecedents of happiness among pregnant women were 1) intrapersonal characteristics, 2) reproductive history and related characteristics, 3) interpersonal relationship, and 4) external factors. The consequences included 1) pregnant women's well-being, 2) fetal well-being, 3) maternal well-being, and 4) child's happiness. CONCLUSION: Although further studies are required to refine the diverse attributes of the concept, the results of this study contribute to explaining happiness among pregnant women. In addition, the development of adequate interventions to increase prenatal happiness is needed.